ASSESSMENT OF SEVERITY HEARING LOSS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - simovic, sladjana stanimir (Medicinski časopis, 2017)
ABSTRACT Objective: The purpose of this study was to determine diabetes mellitus tip 2 influence to incidence and severity of sensorineural hearing loss. Metods: The prospective case control study was done during 2013. among 124 patients, age range 21-84 years, who was admitted to ENT department of the Health Center Kragujevac for evaluation of hearing loss. We performed detailed history, complete otorhinolaryngological examination including otoscopy, tympanometry and tonal liminal audiometry. All subjects were divided into two groups. The study group consisted 67 patients with diabetes mellitus tip 2 and the control group included age and gender matched subjects. We used tonal liminar audiometry for evaluation the existence and degree of hearing loss. The mean value obtained by tonal liminar audiometry at frequencies of 500, 1000, 2000 and 4000 Hz, greater than 25 dB is considered as a hearing loss. Data was statistically analyzed with descriptive statistical methods, t- test and χ2-test using by standard statistical software package (SPSS for Windows, version 19.0). Results: There is sensorineural hearing loss in all patients with diabetes mellitus type 2. The frequency and degree of sensorineural hearing loss were statistically significantly higher in group with diabetes mellitus patient compared to control group (p < 0,05). Conclusion: The results indicate that diabetes mellitus type 2 often have a significant hearing loss, which is very easy to establish using by tonal liminar audiometry, suggesting that these patients should be refer to the assessment of impairment. Keywords: diabetes mellitus, sensorineural hearing impairment, tonal liminar audiometry.